NETWORK TECHNOLOGY OF ADVANCED TRAINING COURSE - Vyacheslav A. Starodubtsev; Antonina A. Kiseleva (Высшее образование в России)
The article examines the model of the blended process of the formal and non-formal professional growth of higher education instructors and the organization of the network course of teacher’s training with the participation of content’s curator. The need of creating the mechanisms of acknowledgement (validation) and certification of the non-formally acquired competences of scientific-pedagogical personnel of higher education is shown.